Optimization based approach to solve phase balancing problem in the distribution system - CEYLAN, OĞUZHAN (My University, 2023)
With the changes occurring in the power distribution systems, such as the inclusion of new loads and sources such as electric vehicles and renewable energy sources the unbalance factor increases, which may lead an increase in system losses, and voltage unbalance. Thus, remedial actions to balance the power distribution systems are needed. To solve this problem, this paper proposes an approach, that considers phase switching, reactive power supports from PV s, and tap operations of the voltage regulators into consideration. The proposed model is tested on a modified IEEE 123 Bus Test System with photovoltaics and electric vehicles. A recently developed heuristics algorithm named Grey Wolf Optimization method was utilized to perform tests on an instant of time of a day and a daily based simulation. From the results it was observed that using all devices in an hierarchical way is able to solve the voltage unbalance problem.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Mühendislik; Sosyal Bilimler Genel; OTOMASYON & KONTROL SİSTEMLERİ; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENGINEERING; SOCIAL SCIENCES, GENERAL; AUTOMATION & CONTROL SYSTEMS; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; INFORMATION SCIENCE & LIBRARY SCIENCE; ENGINEERING, MANUFACTURING; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Enerji Mühendisliği ve Güç Teknolojisi; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Emniyet, Risk, Güvenilirlik ve Kalite; Kontrol ve Optimizasyon; Information Systems and Management; Social Sciences & Humanities; Energy Engineering and Power Technology; Physical Sciences; Electrical and Electronic Engineering; Safety, Risk, Reliability and Quality; Control and Optimization; grey wolf optimization; optimization; phase balancing; voltage unbalance factor